PENGARUH PENGETAHUAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DASAR DAN KETERAMPILAN KERJA TERHADAP KINERJA KARYAWAN UNIVERSITAS PAMULANG (UNPAM) TANGERANG SELATAN - jartono, Supri (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The quality of institutional services becomes a challenge that can not be ignored as a manifestation of human resource professionalism not to mention employees in Pamulang University South Tangerang. The facts show that not all UNPAM work unit services are optimal. In the library services that look for books and catalogs that are expected to facilitate the responded visitors agreed under the proportion of 50%. This condition indicates that the performance of employees UNPAM South Tangerang not yet optimal. The purpose of this study is to analyze the influence of basic communication technology and information ( ICT) knowledge and work  skills on employee performance. The research method used is survey. The research population is the employees of UNPAM with the sample covering work unit based on communication and information technology ie personnel unit, library, and academic faculty. Data analysis technique using path analysis test. The result of the research as follows: 1) there is positive direct influence of basic ICT   knowledge to employee performance (β Y1 = 0,298); 2) There is positive direct effect of work skill to employee performance (β Y2 = 0,593), and 3) direct positive basic  ICT knowledge to work skills (βx21 = 0.663).